The Judicial Function´s Effectiveness in the Brazilian Code of Civil Procedure - Paiva, Danúbia Patrícia De (2016)
The article focuses on the activity of the magistrate considering the paradigm of democratic state, the principles of reasonable duration of the process and cooperation, and the the political function of the Judiciary. It will be presented in three parts, in addition to the introductory part. At first, it narrates the rise of the Judiciary from the legalization and judicial activism. The second part is dedicated to the activity of judges in cases as from the Law 13.105. At the end, the conclusions on the contribution of procedural rules in relation to the slowness, democratization of justice and judicial efficiency.